(untitled) (Research, Society and Development, 2022)
Objective: To understand the impacts of the COVID-19 pandemic on health education actions in Primary Care. Methodology: this is an integrative literature review, with a qualitative approach. Articles, dissertations, theses and institutional documents were used between April and May 2022 in the following databases: Virtual Health Library, MEDLINE, Scielo, academic google and Ministry of Health. Articles published in Portuguese and English, with full text, available online, which portrayed the topic addressed, were selected. Results: Faced with the pandemic, some changes were necessary in the organization of care in the Unified Health System, due to the overload by the demand for routine care, the need to offer health care in urgency, emergency and intensive care resulting from the complications caused by COVID-19. In this way, health education is considered an important tool with transformative power in facing the disease to empower people to prevent and control COVID-19 more effectively. The use of Information and Communication Technologies (ICTs) including the use of social networks to disseminate information was also perceived in the results of the study. Conclusion: Quick consultations, with little dialogue and difficulty in access, contributed to the distance in the professional-user relationship in health services and in the development of educational activities imposed by the pandemic. On the other hand, people began to seek more information about health, and for this, health professionals used different virtual sources, which intensified the use of ICT.